PERAN BRAND IMAGE MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP REPURCHASE INTENTION KONSUMEN PRASANTHI TEXTILE DI GIANYAR(Studi pada Konsumen Prasanthi Textile di Gianyar) - Anak Agung Istri Mas Maharani; I Wayan Santika (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2026)
This study aims to examine the role of brand image as a variable that mediates the influence of social media marketing on repurchase intention. The study was conducted on Prasanthi Textile consumers in Gianyar Regency using a quantitative approach using the associative method, and sample determination through a non-probability sampling technique with a purposive sampling method, resulting in 120 respondents as the research sample. Data collection was carried out through a survey with a questionnaire instrument distributed directly and online. The theory used in this study is the Consumer Behavior Model. The data analysis technique applied was path analysis with the help of SPSS software and the Sobel test to test the mediation role. The results showed that social media marketing had a positive and significant effect on repurchase intention and on brand image, while brand image had a positive and significant effect on repurchase intention. Brand image was proven to be able to partially mediate the influence of social media marketing on repurchase intention of Prasanthi Textile consumers. The influence of social media marketing on repurchase intention showed a greater contribution through the mediation role. The implications of this research emphasize the importance of Prasanthi Textile to improve the quality of social media content, strengthen interactivity and engagement with consumers, and maintain consistency in delivering brand information to build a positive brand image and encourage increased consumer repurchase intention.